2019
DOI: 10.3390/jcm8101626
|View full text |Cite
|
Sign up to set email alerts
|

A Virus-Derived Immune Modulating Serpin Accelerates Wound Closure with Improved Collagen Remodeling

Abstract: Numerous treatments have been developed to promote wound healing based on current understandings of the healing process. Hemorrhaging, clotting, and associated inflammation regulate early wound healing. We investigated treatment with a virus-derived immune modulating serine protease inhibitor (SERPIN), Serp-1, which inhibits thrombolytic proteases and inflammation, in a mouse excisional wound model. Saline or recombinant Serp-1 were applied directly to wounds as single doses of 1 μg or 2 µg or as two 1 µg bolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 80 publications
(105 reference statements)
2
42
0
Order By: Relevance
“…In prior work neurotrophin-3 (NT3), a neurotrophic growth factor that promotes proliferation of neural stem cells, enhanced functional recovery after SCI in rats when delivered by chitosan-collagen carriers [21,41]. We recently reported that Serp-1 maintains function when released from chitosan-collagen in vivo in a full-thickness wound healing model [42]. Thus, we pursued this mode of delivery for SCI treatment in our model.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior work neurotrophin-3 (NT3), a neurotrophic growth factor that promotes proliferation of neural stem cells, enhanced functional recovery after SCI in rats when delivered by chitosan-collagen carriers [21,41]. We recently reported that Serp-1 maintains function when released from chitosan-collagen in vivo in a full-thickness wound healing model [42]. Thus, we pursued this mode of delivery for SCI treatment in our model.…”
Section: Resultsmentioning
confidence: 99%
“…Serp-1 has previously been found to modulate infiltration of both T cells [24,61] and macrophages [3,22,42], dependent on the preclinical model being studied. Immunologically, we found in the current study that CD3-positive T cells, but not macrophages, were reduced more quickly in the area of injury after treatment with Serp-1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations